(untitled) (Research, Society and Development, 2022)
This research aimed to identify the knowledge of nursing students about the process of capturing, donating and transplanting organs and tissues, and to describe the learning of nursing students about the process of capturing, donating and transplanting organs and tissues after obtaining information on the topic. It was a descriptive study, with a qualitative approach, the research subjects were academics from the last period of the undergraduate nursing course who participated in a course offered by a hospital institution and completed two questionnaires offered before and after participating in the course. The collected data were categorized for analysis and interpretation. It was identified an excellent use of academics after participating in the course, improving knowledge in relation to the topic addressed. It was concluded that a future well-educated nurse will be able to intervene positively in relation to the stages of this process of capturing, donating and transplanting organs and tissues for a better performance.